Comparison of utility and organizational impact of reusable and single-use rhinolaryngoscopes in a tertiary otorhinolaryngology department - Gudnadottir, Gunnhildur; Hafsten, Louise; Dahl Travis, Helena; Nielsen, Kirsten; Hellgren, Johan (Frontiers in Surgery, 2024)
BackgroundFlexible rhinolaryngoscopes are an important tool in otolaryngology. In recent years, single-use rhinolaryngoscopes (SURLs), which have been developed as an alternative to reusable scopes (RRLs), offer various advantages including less risk of contamination and elimination of the need for cleaning and reprocessing between procedures. This study aimed to compare procedure efficiency, organizational impact, and economic impact between SURLs and RRLs used for elective procedures conducted outside the otorhinolaryngology department in the hospital environment.MethodsIn this randomized prospective study, either type of endoscope was tested by on-call otolaryngologists over a total of twelve weeks. The organizational impact was investigated using a quantitative research design. All categories of stakeholders responded to specific surveys based on profession; these included doctors (n = 13), those in managerial positions (n = 3), and other healthcare staff including technicians and nurses (n = 11). A micro-costing approach was used to evaluate resource utilization and cost of services. The trial was uploaded to clinicaltrials.gov (ID number: NCT0519821, https://clinicaltrials.gov/study/NCT05198219?intr=rhinolaryngo&rank=1).ResultsOverall, 14 and 12 procedures were performed using the SURLs and RRLs, respectively. No significant differences were observed between the endoscopes in terms of procedure duration, reported image quality, or maneuverability. The SURLs were significantly superior in terms of four organizational impact parameters, namely, modes of cooperation and communication, vigilance and monitoring methods, working conditions and safety, and logistics. The estimated per-procedure cost of the RRLs was SEK 536 (€ 34,68).ConclusionThe cost and effectiveness of RRLs and SURLs is influenced by the healthcare setting, procedure volume, and duration of device use. The adoption of SURLs can improve safety, streamline processes, and potentially reduce the risk of disease transmission.